Perforated Meckel's diverticulum as an uncommon cause of pneumoperitoneum in the newborn: A case report - William G. Lee; Shannon T. Wong-Michalak; Richard C. Judelson; Eveline H. Shue; Juan Carlos Pelayo; Eugene S. Kim (Elsevier, 2024)
Introduction: Pneumoperitoneum in neonates is an ominous sign of gastrointestinal (GI) perforation which often requires emergent surgical intervention. Although Meckel's diverticulum (MD) is the most common congenital anomaly of the GI tract, spontaneous MD perforation leading to pneumoperitoneum in the immediate postnatal period is an extremely rare occurrence. This report describes the case of a perforated MD presenting as pneumoperitoneum on day of life (DOL) one. Case presentation: A 1-day-old 36 week gestational age male presented with acute abdominal distention and guarding upon examination. Two-view abdominal radiographs revealed pneumoperitoneum without pneumatosis intestinalis, portal venous gas, or bowel dilation. Exploratory laparotomy was performed and bilious ascites was encountered - secondary to a perforated MD in the distal ileum. The perforated MD and adjacent small bowel were resected and a double-barrel ileostomy was created. He recovered successfully and without complication in the acute postoperative period. Histopathologic findings were consistent with a perforated MD with ectopic pancreatic tissue. Conclusion: This rare case highlights the importance of early surgical intervention for neonates with pneumoperitoneum secondary to a perforated MD. Heightened clinical suspicion for a perforated MD should be considered among term/late preterm neonates presenting with pneumoperitoneum and low suspicion for necrotizing enterocolitis.